The legality of using the United Nations Security Council to bind third parties to the Rome Statute - Mrewa, Loyce (Department of Public Law, 2017)
The consequential problems emanating from the linkages between law and politics in the international sphere will be examined in this dissertation. In particular, the SC referral mechanism to the ICC and its associated problems will be explored. The primary focus will be an investigation of the procedure used to refer a situation to the ICC, provided in Article 13 (b) of the Rome Statute.